Implementation of voice over Internet Protocol using session initialization protocol - Chua, Eng Huat. (2008)
VoIP represents the next generation in communication services. By moving voice services to the data network, we are able to eliminate a separate and managed voice infrastructure and dramatically reduce the cost of communication service. The advantages of selecting IP telephony include providing accommodation of long-range developments.